1939
DOI: 10.1098/rspb.1939.0033
|View full text |Cite
|
Sign up to set email alerts
|

The mechanical efficiency of frog’s muscle

Abstract: The factors determining the maximum work and the mechanical efficiency of muscle were discussed by Hartree and Hill in 1928. Work was measured with the Levin-Wyman ergometer (Levin and Wyman 1927), the muscle being allowed to shorten at constant speed, adjustable as required, and recording a tension-length curve on a smoked surface. The whole of the work which the muscle can do in a single shortening at the given speed is thus obtained, as in no other method. The mechanical efficiency, therefore, should be the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1963
1963
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(14 citation statements)
references
References 2 publications
(4 reference statements)
1
13
0
Order By: Relevance
“…WO7ODS different speeds depends on many factors, but forces up to 1-8 Po have been reported (Katz, 1939;Abbott, Aubert & Hill, 1951). Hill (1939) showed that maximum efficiency of muscle shortening occurs at 0-2 Vmax* We found subjects cycled with maximum efficiency at speeds of rev/mill, a conclusion which can also be drawn from the work of Asmussen (1952) and Banister & Jackson (1967) (Fig. 2).…”
Section: Discussionsupporting
confidence: 74%
“…WO7ODS different speeds depends on many factors, but forces up to 1-8 Po have been reported (Katz, 1939;Abbott, Aubert & Hill, 1951). Hill (1939) showed that maximum efficiency of muscle shortening occurs at 0-2 Vmax* We found subjects cycled with maximum efficiency at speeds of rev/mill, a conclusion which can also be drawn from the work of Asmussen (1952) and Banister & Jackson (1967) (Fig. 2).…”
Section: Discussionsupporting
confidence: 74%
“…9A). Mechanical efficiency for ramp shortening had a maximum value of 0-36 at about 1/5 VI; the peak of the efficiency preceded the peak of the power (about 1/3 VO), as already described for whole frog sartorius muscle by Hill (1938Hill ( , 1939. For staircase shortening the efficiency was lower than during ramp shortening.…”
Section: Consequently While For Velocities Lower Than 0 4 Lo S-'mentioning
confidence: 89%
“…As maximal tension is known to develop early in a skeletal or cardiac muscle twitch, and thereafter progressively and more slowly to decline, maximal external work can only be obtained if there is an early rapid increase in load followed by a progressive decline to match precisely the early rise and slower decline in tension. These conditions have been reproduced experimentally for skeletal muscle (2,35).…”
Section: Cn_1mentioning
confidence: 99%
“…In skeletal muscle at a particular initial length, and in heart muscle at a particular length and inotropic state, the extent and speed of shortening and the efficiency of the contraction depend upon the load (2)(3)(4)(5). In an earlier study we showed that in the normal conscious dog at rest the systemic load and the left ventricle were so matched that during contraction maximal external work was done and maximal power was transferred to the systemic circulation (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation